Cadmium (Cd) Resistance of Isolate Bacteria from Poboya Gold Mining in Palu, Central Sulawesi - Fahruddin Fahruddin; Syahruddin Kasim; Eka Ummi Rahayu (Universitas Mataram, 2020)
The mining industry in Indonesia is growing rapidly, giving an environmental impact from the waste produced because it contains dangerous heavy metals, one of which is cadmium metal (Cd). The purpose to know the ability of cadmium resistance in bacterial isolates. Bacterial isolates were obtained from soil samples from the Poboya Gold Mine field, Palu. Bacterial isolation and selection were carried out by the plate count method, resistance testing using nutrient broth media containing heavy metals Cd, analysis of Cd concentrations using atomic absorption spectrophotometers. From the results of the study, four types of Cd resistant isolates were obtained based on macroscopic and microscopic characterization results, namely isolates EK1, EK2, EK3 and EK4. The two best isolates of Cd resistance, EK2 and EK4 isolates were tested on media containing 20 ppm Cd, showing that both of these isolates were able to significantly reduce Cd concentrations in the supernatant and pellets.